TINGKAT KELAINAN SEL PURKINJE HETEROTOPIK HUBUNGANNYA DENGAN PERBEDAAN SENSITIVITAS ANTARA LOBUS ANTERIOR DAN POSTERIOR DARI CEREBELLUM TIKUS TERHADAP RADIASI SINAR-X - Win Darmanto (The East Java Biological Society, 2004)
Our previous experiment showed that prenatal exposure of rats to X-radiation in the late gestation period causes heterotopic Purkinje cells in the internal granular layer (IGL) of the cerebellum. The present study demonstrated precisely the involvement of Reelin in the aligment of Purkinje cells, which are different in severity between anterior and posterior lobes. Pregnant rats were exposed to 2.5 Gy X-radiation on gestation day 21 and the cerebellum of progeny was examined histologically and by immunohistochemistry of IP3 Receptor to identify Purkinje cells. By P8, while Purkinje cells with well developed dendrites aligned underneath the EGL in the control cerebellum, Purkinje cells with shorter and abnormally oriented dendrites failed to align and remained in the heterotopic location in the IGL of the anterior lobes but a small number of heterotopic Purkinje cells formed in the posterior lobes of the irradiated rats. Our previous published Reelin is present in the premigratory zone of the EGL and IGL in the control cerebellum. It decreased in the irradiated cerebellum on P1 to P8, especially the anterior lobes, however in posterior lobes on P8 Reelin level compared to the control (Darmanto, 2003). It is thus indicated that anterior lobes are more sensitive to X-radiation than posterior lobes and the different levels of Reelin between anterior and posterior lobes caused by X-irradiation may contribute the different susceptibility in induction of derangedPurkinje cells.